UPAYA PEMANFAATAN LIMBAH SABUT KELAPA MENJADI POT BUNGA SERTA SOLUSI PEMASARAN UNTUK MENUNJANG PEREKONOMIAN WARGA DESA PENGALIHAN DI ERA PANDEMI COVID-19 - Eliah Siregar; ANDRIANSYAH (Indra Institute Research & Publication, 2021)
This study aims to determine the Efforts to Utilize Coconut Coir Waste into Flower Pots as well as Marketing Solutions to Support the Economy of the Pengalih Village Residents in the Era of the Covid-19 Pandemic. This research has been carried out in the Pengalihan Village, Enok District, Indragiri Hilir Regency. The determination of the research location was carried out intentionally (porposively) during KKN activities in the Pengalihan Village and with the consideration that the Pengalihan Village is one of the coconut production center villages. The time of conducting the research begins on August 5 to September 25, 2021. The analysis used is to increase community income through efforts to use coconut coir waste into flower pots and marketing solutions to support the economy of the residents of the Pengalih Village in the Covid-19 Pandemic Era in the Pengalihan Village, Enok District. The results of the study were the initial conditions that occurred in the midst of the transfer village community, namely the occurrence of community economic problems that were impacted by the covid'19 pandemic, and the lack of public knowledge about the use of coconut coir waste. become flower pots so that they are able to help and support the economy of the residents of the Pengalihan Village in this Covid'19 Pandemic Era.